2014
DOI: 10.4204/eptcs.150.2
|View full text |Cite
|
Sign up to set email alerts
|

Formal Safety and Security Assessment of an Avionic Architecture with Alloy

Abstract: We propose an approach based on Alloy to formally model and assess a system architecture with respect to safety and security requirements. We illustrate this approach by considering as a case study an avionic system developed by Thales, which provides guidance to aircraft. We show how to define in Alloy a metamodel of avionic architectures with a focus on failure propagations. We then express the specific architecture of the case study in Alloy. Finally, we express and check properties that refer to the robust… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 4 publications
0
18
0
Order By: Relevance
“…In this work, the security aspects are not developed (we have just considered three threats that have the same kind of effects as failures). However, recent works have showed the relevance of Alloy to assess more advanced security properties [10,11,6]. Moreover, it was shown that using AltaRica, one can specify the effect of richer security threats over a system architecture [2] and check related security properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, the security aspects are not developed (we have just considered three threats that have the same kind of effects as failures). However, recent works have showed the relevance of Alloy to assess more advanced security properties [10,11,6]. Moreover, it was shown that using AltaRica, one can specify the effect of richer security threats over a system architecture [2] and check related security properties.…”
Section: Discussionmentioning
confidence: 99%
“…Alloy has recently been used in the context of security assessment, for instance to model JVM security constraints [11], access control policies [12], or attacks in cryptographic protocols [10]. Besides, we proposed in earlier works a study of the safety and security assessment of an avionic system supporting an approach procedure [4,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Alloy does support multiple levels of abstraction as well as recursively defined relations but not recursive functions. Concurrent systems can be modeled in Alloy (see, eg, the work of Brunel et al). As Alloy is based on relational logic and relational calculus, nondeterminism is already present .…”
Section: Assessment Of Selected Formal Methodsmentioning
confidence: 99%
“…On the other hand, this can be much more powerful than most explicit mechanisms, because one can write a fully relational postcondition, which is not possible in many other methods. Alloy has been used for designing systems where global system properties of correctness , such as safety, security, and reliability, have played an important role (see, eg, the work of Brunel et al). Alloy has no direct notion of time .…”
Section: Assessment Of Selected Formal Methodsmentioning
confidence: 99%
“…If the major part of the paper contributions relates to adaptations, there are also some novel and/or disruptive approaches, e.g. Sommerville [41], Olive et al [42], Knorreck and Apvrille [43], Pedroza et al [44], Apvrille and Roudier [45] and Brunel et al [46,47].…”
Section: Improving Safety Engineering With Security Considerationsmentioning
confidence: 99%